Pengaruh Kurikulum Merdeka Terhadap Hasil Belajar Siswa Kelas IV di SDN 106184 Sekip Lubuk Pakam Tahun Ajaran 2022/2023 - Agustin, Riska; Hidayat, Wahyu; Lubis, Rizka Hidayah Husin (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to examine the impact of the independent curriculum on student learning outcomes in Indonesia, particularly at SD Negeri 106184 Sekip Lubuk Pakam. The research employs a quantitative approach using a Quasi-Experimental design. The sample for this study was selected through total sampling, involving all 32 fourth-grade students at the school, with 16 students in Class A as the experimental group and 16 students in Class B as the control group. The findings reveal a significant effect of the independent curriculum on students' learning outcomes, specifically in the science subject matter related to the identification of energy sources and forms. Data analysis was conducted using the Wilcoxon test, which indicated that the Asymp Sig value was lower than the significance level (0.002 < 0.05). These results suggest that the implementation of the independent curriculum positively influences students' learning achievements.